The value and benefits of using seasonal climate forecasts in agriculture: evidence from cowpea and sesame sectors in climate-smart villages of Burkina Faso - Ouédraogo, Mathieu; Zougmoré, Robert B.; Barry S; Somé, Léopold; Grégoire B (2015)
This infonote summarizes initial findings of a project entitled “Impact of communicating seasonal climate forecasts to cowpea and sesame farmers in Yatenga region, North Burkina Faso’” undertaken during the 2014 main agricultural season by scientists from the CCAFS West Africa programme and the Institut de l’Environnement et de Recherches Agricoles (INERA), Burkina Faso. Sesame is a cash crop promoted in recent years to respond to a growing global demand. Quite versatile and produced across the country, yields remain low with an average of 300-350kg/ha. National production was estimated at around 60,000 tons in 2012, mostly for export. Cowpea is a key legume crop, mostly cultivated by smallholder farmers in intercropping with cereals (95%). Yields are low (around 300kg/ha) while it could reach 1,500kg/ha in monoculture. Just a minority (5%) of farmers use modern inputs (improved seeds, fertilizer) and market their grain for the regional market. This project aims at assessing:  The effect of climate information services on farm productivity and incomes for cowpea and sesame farmers in the Yatenga region;  Farmers’ willingness to pay for such climate information services  Lessons learned for potential scaling up of communicating climate forecasts services in the cowpea and sesame sector as a way to improve farmer climate resilience and productivity. Such studies are also being carried out in climate-smart villages in Senegal (Kaffrine region).